Development of E-Module Teaching Materials Gymnastics Learning Theory and Practice Course (Journal of Physical Education Health and Sport, 2022)
This study aims to develop and test the effectiveness of e-module teaching materials for the theory and practice of gymnastics learning. The methodology used is development research with 10 stages of development referring to the Borg and Gall development steps. However, in this study only through 4 stages including; (1) Research and Information collection, (2) Planning, (3) Developing a Preliminary form of Product, and (4) Preliminary Field Testing. The results of the media expert validation assessment show that the average percentage result is 82.6% with a valid category and can be used with revisions, while the results of the material expert validation assessment results get an average percentage result of 86.5% with a very valid and usable category, and the results of the assessment learning expert validation obtained an average percentage result of 81% with a valid category and can be used with revisions. Furthermore, based on the results of the small-scale test, the results obtained are 77% with the category "Fair/Attractive/Good. Thus, it can be concluded that the results of developing an e-module for the theory and practice of gymnastics learning courses are feasible to be used as teaching materials.